Violência nos espaços intraurbanos: dinâmica dos homicídios dolosos no território manauara - Gama, Arnaldo Costa (2023)
Throughout history, we have witnessed transformations in the urban space of major Brazilian cities, largely due to various historical processes and specific factors occurring in the urban fabric, such as industrialization, increased population density intensifying the process of urbanization, migration, and the sociability of urban spaces leading to various socio-economic problems, including violence, poverty, and social inequality. The main objective of this study is to analyze violence from the perspective of the spatial dimension of Intentional Homicides (IH) that occurred within the urban space of the municipality of Manaus, from 2012 to 2020, considering that intentional homicides are one of the main issues affecting the intraurban spaces of Brazilian metropolises. This research is based on exploratory data analysis, which takes into account the heterogeneity of the urban space and its sociodemographic characteristics of the population, as well as the socio-spatial segregation of the municipality within spatial boundaries. The intentional homicides are studied from a cross-sectional perspective by considering their distribution within the intraurban spaces, their relationship with the dynamics of socio-spatial segregation, their association with urban facilities, and the analysis of satellite images to observe spatial patterns. The study also examines the sociodemographic characteristics of the victims and perpetrators, their association with urban facilities, and the influence of criminal organizations in committing these crimes. The research observes the transformations that have occurred in the capital of Amazonas and how they relate to the phenomenon of intentional homicides. The data used for this research is sourced from the Public Security Department of Amazonas (SSP/AM). The spatial format of the data allows the application of spatial techniques such as distance measures, kernel interpolation, spatial autocorrelation, and multiple regression. The results reveal a concentration of homicide crimes in the Southern, Western, and Northern zones of the municipality, with high rates of homicides occurring in densely populated areas with higher social vulnerability, mostly associated with drug trafficking. Firearms are the most commonly used means for committing such crimes, and the perpetrators are often unknown. There is a strong correlation between homicides and the young population (aged 15 to 29 years). This phenomenon distinguishes Manaus from other Brazilian municipalities due to the prevalence of such crimes, with involvement in the drug retail trade coming from the Northern Brazilian tri-border region. As a result, it was possible to observe that these crimes exhibit different spatial distributions over time.